Assisted dying in the Aotearoa New Zealand media: a critical discourse analysis. (2nd January 2022) - Booth, Amanda; Blake, Denise
ABSTRACT: Death by assisted dying has long received media attention and remains a current socio-political health topic today. For many, understanding assisted dying is derived from media representations that position health, illness and dying in particular ways. These various stories shift and shape how we understand ourselves. With a Foucauldian lens, we explore what the media made possible for people to think, feel and do in relation to this phenomenon. From media articles collated in early 2018 we identify representations of a particularly individualised "autonomy' which intersects with assisted dying as a 'right' and necessary 'choice' to control when, where and how to die. Those with mental illness were excluded from this discourse for lacking a 'rational' sensibility. From the autonomous right to choose discourse, two subject positions arose; my choice and mine alone and the defender of rights . A counter-discourse positioning assisted dying as perilous for society and the subject position of concerned protector emerged in resistance to the autonomous right to choose . A particularly Western and privileged subject was representative of those in favour of legitimating the practice. Non-Western understandings were absent, religious and spiritual considerations marginalised, the disabled body let die, and the older adult voice silent.